2009
DOI: 10.1111/j.1476-5381.2009.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of biosynthesis and modes of action of prostaglandin E2 and prostacyclin in guinea pig mesenteric lymphatic vessels

Abstract: Background and purpose: Rhythmical transient constrictions of the lymphatic vessels provide the means for efficient lymph drainage and interstitial tissue fluid balance. This activity is critical during inflammation, to avoid or limit oedema resulting from increased vascular permeability, mediated by the release of various inflammatory mediators. In this study, we investigated the mechanisms by which prostaglandin E2 (PGE2) and prostacyclin modulate lymphatic contractility in isolated guinea pig mesenteric lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 35 publications
(94 reference statements)
4
35
0
Order By: Relevance
“…Our data confirm the pivotal role played by K ATP channels in regulating lymphatic pumping (25,30,39,45,52,58), as evidenced by the potent action of cromakalim to hyperpolarize lymphatic muscle and abolish the phasic contractions that mesenteric lymphatics characteristically exhibit (Fig. 2).…”
Section: Role Of No In Inflammation-induced Pumping Inhibitionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our data confirm the pivotal role played by K ATP channels in regulating lymphatic pumping (25,30,39,45,52,58), as evidenced by the potent action of cromakalim to hyperpolarize lymphatic muscle and abolish the phasic contractions that mesenteric lymphatics characteristically exhibit (Fig. 2).…”
Section: Role Of No In Inflammation-induced Pumping Inhibitionsupporting
confidence: 86%
“…improvement of pumping with indomethacin reported in the same TNBS model (60) strongly suggest a role for products of arachidonic acid metabolism. Prostacyclin and prostaglandin E 2 (PGI 2 and PGE 2 ) have been directly associated with lymphatic pumping inhibition in the same mesenteric preparation (8,45). Action of these mediators could further explain the incomplete effect of 1400W in restoring contractile activity in vessels from TNBS-treated animals.…”
Section: Role Of No In Inflammation-induced Pumping Inhibitionmentioning
confidence: 95%
See 1 more Smart Citation
“…In line with their vasodilatory/relaxing actions typically observed in other smooth muscles, nitric oxide and prostanoids, such as prostaglandin E 2 and prostacyclin, cause the lymphatic muscle to hyperpolarize and the pumping activity to slow down. 17,20,22,28,29 Endothelium-derived thromboxane A 2 , on the other hand, induces a depolarization as well as an increase in electrical activity (STDs and APs) and lymphatic vessel contraction frequency. 11,[30][31][32] We confirmed that, in wire-myograph-mounted vessels, endothelial function was compromised, as contractile and Vm responses were not affected by treatment with nitric oxide synthase and cyclooxygenase inhibitors, while the same inhibitors depolarized the Vm in unstretched vessels by about 10 mV.…”
Section: Fig 1 Electrophysiological Characteristics Of Rat Mesentermentioning
confidence: 99%
“…In particular, prostaglandin (PGE 2 ) and prostacyclin (PGI 2 ) have been reported to relax lymphatic muscle and inhibit pumping of both bovine and guinea pig mesenteric lymphatic vessels in a concentration-dependent manner (8,42,55). PGE 2 and PGI 2 have been proposed as mediators of the compromised contractility of mesenteric lymphatic vessels observed in an animal model of intestinal inflammation, because COX inhibitors partially restore contractility (8,42,55). In addition to responses to exogenous prostanoids, lymphatic vessels have been reported to be capable of producing PGE 2 and PGI 2 (42).…”
Section: Observed Changes May Be Due To Mesenteric Venous Hypertensiomentioning
confidence: 99%